Is restless legs syndrome in Parkinson disease patients associated with any specific factor? - Manoel Alves SOBREIRA-NETO; Márcio Alexandre PENA-PEREIRA; Emmanuelle Silva Tavares SOBREIRA; Marcos Hortes Nisihara CHAGAS; Carlos Maurício Oliveira de ALMEIDA; Regina Maria França FERNANDES; Vitor TUMAS; Alan Luiz ECKELI (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Restless legs syndrome or Willis-Ekbom disease is a disorder characterized by unpleasant sensations associated with the need to mobilize the lower limbs. In Parkinson disease patients, restless legs syndrome is associated with worse quality of life and excessive sleepiness. Regarding other factors, results of different studies are controversial. Objective: To determine the factors associated with the restless legs syndrome presence in Parkinson disease patients. Methods: A cross-sectional study was conducted in 88 consecutive Parkinson disease patients from the outpatient clinic for 21 months. Participants underwent a clinical interview, assessment based on standardized scales (Epworth Sleepiness Scale, Parkinson Disease Questionnaire - 39, Pittsburgh Sleep Quality Index, International Restless Legs Syndrome Study Group rating scale), and video-polysomnography. Results: Out of the 88 participants, 25 had restless legs syndrome. In the multivariate analysis, restless legs syndrome in Parkinson disease has been associated with the symptom of smell loss and quality of sleep and life. In the univariate analysis, restless legs syndrome in Parkinson disease has occurred more frequently in women with higher frequency of insomnia, constipation, and anosmia than in the group without restless legs syndrome. Conclusion: Restless legs syndrome is a prevalent condition in patients with Parkinson disease and is associated with specific characteristics in this group of patients.